MSPT: an open-source motion simulator for proton therapy. (21st September 2015) - Morel, P; Flynn, R T; Gelover, E; Blin, G; Vialette, S; Wu, X; Wang, D
Abstract: The dosimetric benefits of proton therapy may be greatly degraded when the tumor or organs move during the treatment. Hence, mitigation or adaptive methods have become topics of research interest. These techniques require dose computation on time-dependent patient geometry. We developed an open-source four-dimensional dose computation and evaluation software, Motion Simulator for Proton Therapy (MSPT), for the spot-scanning delivery technique. It aims at highlighting the impact of the patient motion during a treatment delivery by computing dose on the moving patient. The main interest of this simulator lies in the ability to render the impact of a predicted patient motion on a prescribed treatment plan. MSPT used proton pencil beam algorithm for dose computation, and the dose in patient geometry computed by MSPT was able to match that computed by the commercial treatment planning system. MSPT was able to render the impact of motion on patient data sets. This capability makes it an innovative research tool to evaluate and compare different methods of motion management or mitigation. The open-source feature makes it appealing, since it is intended to evolve, to be improved and to be the starting point of new research on patient motion in proton therapy.